103k views
0 votes
Please I need help Asap!!!!

Please I need help Asap!!!!-example-1
User Wenger
by
5.9k points

1 Answer

4 votes

Answer:


h = -3\\k = 3


a^2 = 25\\b^2 = 9


((x+3)^2)/(25) + ((y-3)^2)/(9) = 1

Explanation:

The general equation of an ellipse is as follows:


((x-h)^2)/(a^2) + ((y-k)^2)/(b^2) = 1

Where the point (h, k) is the center of the circle

a is called semi major axis: horizontal distance from the ellipse to its center

b is the semi minor axis: vertical distance from the ellipse to its center.

See the attached image.

There you can notice that


a = 5\\\\a^2 = 25\\\\b = 3\\\\b^2=9

The center is at point (-3, 3)

Thus:


h = -3\\k = 3

Then the equation sought is:


((x-(-3))^2)/(5^2) + ((y-3)^2)/(3^2) = 1

Simplify


((x+3)^2)/(5^2) + ((y-3)^2)/(3^2) = 1

Please I need help Asap!!!!-example-1
User Colin Hebert
by
6.2k points